Electrotunable coupling between an epsilon-near-zero thin film and conducting polymer nanoantennas - Yulong Duan; Suraya Kazi; Dongqing Lin; Longzhu Liu; Magnus P. Jonsson (Proceedings of the National Academy of Sciences, 2026)
Plasmonic resonances in nanostructured conducting polymers provide a compelling route to actively tunable nanophotonics and metasurfaces, owing to their ability to be dynamically modulated through electrochemical doping. Although their lower mobility limits resonance quality compared to noble metal plasmonics, we experimentally demonstrate that the resonances of conducting polymer nanoantennas can effectively couple to epsilon-near-zero (ENZ) mode of an underlying thin indium tin oxide layer, in a manner analogous to noble metal plasmon–ENZ interactions. We show that the coupling strength can be modulated reversibly via electrical bias or chemical redox control, enabling dynamic tuning of electromagnetic field enhancement in the ENZ layer with a modulation depth exceeding 90%. These findings establish conducting polymer nanoantennas as a versatile platform for reconfigurable ENZ-based photonic systems, paving the way for nanophotonic devices with tunable linear and nonlinear optical functionalities.